Evaluación poblacional del pez exótico trichopodus trichopterus “gurami” y los posibles impactos sobre las especies nativas en aguas lindantes a la ciudad de Iquitos, Loreto, Perú - Chuquipiondo Guardia, Carlos Tobias (2023)
The exotic fish Trichopodus trichopterus, popularly known as gourami, is a species native to Asia, which has been introduced globally, being present in all continents of the world. This species has all the necessary characteristics to be considered a "dangerous" exotic species for natural environments, being necessary to carry out studies to determine its possible impacts on natural environments. In this context, the main objective of this study was to evaluate the populations of gourami and their possible impacts on native species in waters adjacent to the city of Iquitos, Peru. The results of the study revealed the presence of the gourami in more than 70% of the sampled premises, with dominance of approximately 30% in relation to the presence of other fish species; The stomach contents revealed the presence of food items that helped determine that this species is generalist and opportunistic; the physical and chemical parameters of the water allowed us to observe that the gourami is capable of inhabiting oxygen-poor environments with high levels of ammonium. With regard to the parasitological analyses, monogenoids of Trianchoratus acleitrhrum, a species native to Asia, were identified. It is concluded that the gourami may be affecting the diversity of individuals and richness of species in water bodies of the Peruvian Amazon by presenting characteristics that allow us to infer that the gourami can compete for space and food with native fish species, as well as could transmit to Amazonian fish some type of parasites typical of another continent. This study will serve as an important baseline for future research on the impacts of the gourami on Amazonian aquatic ecosystems.